Comparison of parental reports of smoking and residential air nicotine concentrations in children. Issue 11 (15th August 2006) - Gehring, U; Leaderer, B P; Heinrich, J; Oldenwening, M; Giovannangelo, M E C A; Nordling, E; Merkel, G; Hoek, G; Bellander, T; Brunekreef, B
Abstract : Background: Using questionnaires to assess children's residential exposure to environmental tobacco smoke (ETS) may result in misclassification from recall and response bias. Questionnaire data have frequently been validated against urinary cotinine measurements, but rarely against actual measurements of residential air nicotine. Objective: To compare questionnaire reported smoking with air nicotine concentrations in a large population of children and with urinary cotinine levels in a subpopulation; and to assess the potential impact of the symptom status of the children on the agreement between different measures of exposure. Methods: The authors assessed residential exposure to ETS in 347 German, 335 Dutch, and 354 Swedish preschool and schoolchildren by questionnaire and air nicotine measurements, and in a subset of 307 German children by urinary cotinine measurements. They then compared the different measures of ETS exposure. Results: In all countries, air nicotine concentrations increased with increasing questionnaire reported smoking in a dose-response fashion. Specificity and negative predictive values of questionnaire reports for nicotine concentrations were excellent. Sensitivity and positive predictive values were moderate to good. Excluding occasional smokers, the overall percentage of homes misclassified was 6.9%, 6.7%, and 5.1% in Germany, the Netherlands, and Sweden, respectively. Similar results were found for the agreement of urinary cotinine concentrations with questionnaire reports and air nicotine levels. There was no indication of underreporting by parents of symptomatic children. Conclusion: Despite some misclassification, questionnaire reports are an inexpensive and valid estimate of residential ETS exposure among preschool and school children.